Measuring the Performance of Zakat Management Baitul Mal Aceh Based on Maqashid Sharia Index - Azzuhra, Alfia; Desiana, Rina; Fitria, Ana (International Journal of Zakat, 2025)
This study aims to measure the performance of zakat management in Baitul Mal Aceh to achieve the goals of Abu Zahrah's sharia maqashid which has three main concepts, namely Tahzib Al-Fard (educating individuals), Iqamat Al-'Adl (upholding justice), and Jalb Al-Mashlahah (creating welfare). The data source used is secondary data from Baitul Mal Aceh's financial statements for the 2021-2023 period using a descriptive quantitative method. The results of the research on the concept of Tahzib Al-Fard (educating individuals) were obtained the highest percentage in 2023 with a ratio of 8%. The highest percentage of Iqamat Al-'Adl (upholding justice) with a value of 156% is in 2021, and finally Jalb Al-Mashlahah (creating welfare) in 2023 reaches the highest percentage of 9%. Overall, the measurement of Baitul Mal Aceh's zakat management performance based on the Maqashid Sharia Index resulted in a percentage of 58% or less good in the 2021-2023 period.